Evaluación Presupuestaria al Gobierno Autónomo Descentralizado Parroquial Quinara del Cantón Loja, período 2015 - Mendoza Toledo, Tatiana Fernanda (2016)
This thesis called "BUDGET ASSESSMENT TO THE GOVERNMENT AUTONOMOUS DECENTRALIZED PARISH QUINARA OF LOJA CANTON, PERIOD 2015", was developed in compliance with Regulation of Academic Board of the National University of Loja prior to choose the degree and engineering degree in Accounting and audit Public Accountant Auditor. In order to carry out this thesis work, necessary information was collected, such as the Annual Operative Plan, Budget Execution Status, Income and Expenditure Bills, and contracts for the projects carried out, the same documentation was provided by the President and Secretary-Treasurer of the Parish GAD that served to carry out the respective analysis and application of indicators. In order to meet the objectives of the thesis, budget indicators were applied in order to measure the efficiency, effectiveness and economy of the management of its financial resources, which allowed to verify that the GAD has a high financial dependence, that is to say the resources that Perceived are mostly by transfers from the State, for that reason their financial autonomy is minimal, because it has few activities to capture self-management resources; While in budget reforms the overall percentage for both income and expenditure is low, which is beneficial to the institution. When verifying compliance with the Annual Operational Plan, it was verified that it was carried out in 60,71%, having a default rate of 39,29%. This is mainly due to the failure to reach agreements with the entity that maintains agreements for the performance of several works Could not be met. Finally, a report is presented to the authorities of the Quinara Parish GAD, which contains conclusions and recommendations, which will allow them to take corrective measures to improve the administration of the resources allocated.